Interface water-induced hydrophobic carbon chain unfolding in water. (22nd March 2021) - Xie, Zhang; Li, Zheng; Lou, Gang; Liang, Qing; Chen, Jiang-Xing; Kou, Jianlong; Wei, Gui-Na
Abstract: The folding and unfolding of the carbon chain, which is the basic constitutional unit of polymers, are important to the performance of the material. However, it is difficult to regulate conformational transition of the carbon chain, especially in an aqueous environment. In this paper, we propose a strategy to regulate the conformational transition of the carbon chain in water based on the all-atom molecular dynamics simulations. It is shown that the unfolded carbon chain will spontaneously collapse into the folded state, while the folded carbon chain will unfold with an external electric field. The regulation ability of the electric field is attributed to the electric field-induced redistribution of interface water molecules near the carbon chain. The demonstrated method of regulating conformational transition of the carbon chain in water in this study provides an insight into regulating hydrophobic molecules in water, and has great potential in drug molecule design and new polymer material development.